"Why Can't I See My Friends and Family?": Children's Questions and Parental Explanations About Coronavirus. Issue 1 (27th December 2021) - Haber, Amanda S.; Kumar, Sona C.; Puttre, Hannah; Dashoush, Nermeen; Corriveau, Kathleen H.
ABSTRACT: Question‐explanation exchanges in parent–child interactions foster children's early learning, especially when children are inquiring about unobservable scientific phenomena such as the novel coronavirus (COVID‐19). As with other unobservable entities, children must rely on adults to acquire knowledge about COVID‐19. Yet, we know very little about what children understand about COVID‐19 or its consequences. In our study, we explored developmental changes in children's questions about COVID‐19 and parents' explanations. Parents ( n = 182) of children (aged 3–8) completed an online survey, which included demographic information, parents' explanations, and children's questions. Parents' explanations referenced germs, used illness analogies, and mentioned mitigation strategies . Most of children's COVID‐related questions focused on the consequences of COVID‐19 . Whereas older children asked more about death, younger children asked about loss of activities . The findings advance our understanding of the impact of COVID‐19 on parents and children. LAY ABSTRACT: Young children may rely on parents to acquire knowledge about COVID‐19. Yet, we know very little about what children understand about COVID‐19. We explored children's questions and parental explanations about COVID‐19. We found that parents' explanations referenced germs and compared COVID‐19 to other illnesses. In addition, whereas older (aged 6–8) children asked more about death, younger (aged 3–5) children asked about loss of activities . The findings advance our understanding of the impact of COVID‐19 on parents and children.